Students' Sexual Violence Understanding: Educating XI Grade Students of SMK Muhammadiyah Bojong through the Film “Penyalin Cahaya” - Salsabila, Salma; Fajar, Dwi Ario (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
This study examines sexual violence understanding among 11th-grade students at SMK Muhammadiyah Bojong, influenced by the film "Penyalin Cahaya." Findings show students grasp general concepts well, scoring 91.43 on average for understanding coercion, consent, and impacts of sexual violence. However, specific instances in the film posed challenges, with scores dropping to 66.71, indicating difficulty in distinguishing privacy violations from sexual violence. While "Penyalin Cahaya" effectively educates, students require more nuanced guidance to apply knowledge practically. Integrating such films into the Merdeka curriculum enhances awareness but necessitates clearer distinctions for comprehensive education.